(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
This paper seeks to analyze the performance of the Brazilian State as a producer of health services. The intention isn’t, in any way, to value alternatives to Brazilian model or to solve problems arising from this state performance. On the contrary, it’s to describe the role of the state, in its three spheres, as a producer of health services, pointing to the benefits and harms of the model. Although the objective of this paper is not to present a "better" model, different systems will be described, in an exemplary way, to provide a perspective to the reader about the way the Brazilian state acts in health and how other countries apply their systems.